Avaliação de conjuntos de habitações unifamiliares: análise de manifestações patológicas e vida útil estimada. - Cahino, Jéssika Elaine Mendes (2018)
The housing deficit in Brazil is a problem still found today. Families with medium and low incomes are the most affected in this sense, and these are often subject to low quality or structurally compromised residences, thus living in an environment of risk to health and life. In 2009, the Federal Government implemented an incentive program for Popular Housing, My Home My Life Program (PMCMV), and people from three income brackets could benefit. With the construction of residences on a large scale, concepts such as quality and durability were being left in the background, giving priority to quantity. It was not long before several residences built in the PMCMV period presented pathologies related to all levels, which could be in the planning, design, execution, material quality and / or misuse phases of the structure. Based on the described problem, this research analyzed 46 single-family homes in the city of Palmeira dos Índios / AL, identifying and analyzing the pathologies found, assembling a mapping of the situation, as well as verifying the performance of the residences in relation to the Reference Life ) and Estimated Service Life (VUE) through NBR 15,575 / 2013 and ISO 15,686 / 2011. The method used to verify the VUE was the Factors Method, described by ISO 15.686 / 2011, where factors related to quality, environment and the condition of operation and use were studied for the 46 residences. When comparing VUR and VUE, a reduction of VUR was observed for all analyzed items, thus proving that the dwellings did not meet the standard described. Such reduction of VUR occurred between 22.41% and 33.21%, evidencing a significant reduction, in the absence of periodic maintenance.